2003
DOI: 10.1097/01.rli.0000073446.43445.20
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Metabolic Differences in the Frontal Brain of Depressive Patients and Controls Obtained by 1H-MRS at 3 Tesla

Abstract: The authors demonstrate that absolute quantification of metabolite concentration is essential in properly identifying pathologic differences of brain metabolites in depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(66 citation statements)
references
References 20 publications
1
63
1
1
Order By: Relevance
“…This possibility seemed unlikely because none of the state-of-the-art MRS studies using absolute quantification reported a change in creatine levels in MDD (see the "Discussion" section in the study by Coupland et al 45 ). ( It is noteworthy that 1 study 46 measured an increase in creatine of 16% to 22% in MDD, although this study has not been replicated by others. The overall creatine concentration reported 46 is significantly lower than most other literature values.…”
Section: Commentcontrasting
confidence: 53%
“…This possibility seemed unlikely because none of the state-of-the-art MRS studies using absolute quantification reported a change in creatine levels in MDD (see the "Discussion" section in the study by Coupland et al 45 ). ( It is noteworthy that 1 study 46 measured an increase in creatine of 16% to 22% in MDD, although this study has not been replicated by others. The overall creatine concentration reported 46 is significantly lower than most other literature values.…”
Section: Commentcontrasting
confidence: 53%
“…Patients with affective disorders also exhibit mI deficits in cerebrospinal fluid (34). Although results from in vivo 1 H-MRS studies have been varied with regard to mI levels, potentially due to medication effects (35), some studies have observed reduced basal mI concentrations in the frontal cortex of patients with major depression (36)(37)(38). Furthermore, it may be relevant that patients with affective disorders also exhibit glial cell pathology and reductions in the expression of astrocyte-specific markers in postmortem frontal cortex (39).…”
Section: Discussionmentioning
confidence: 99%
“…We used absolute metabolite levels instead of ratios with creatine to avoid a bias through systematic drifts in the magnitude of the creatine resonance, as suggested by previous studies. 18,[21][22][23][24] VOI tissue segmentation and total hippocampal volume To control for the effect of potential structural differences in the region studied, we assessed tissue composition within the VOIs and total hippocampal volume as follows. The amount of each tissue -grey matter, white matter and CSF -was quantified for each VOI, so the scans were first separated in the 3 different tissues using SPM8 software (Wellcome Trust Centre for Neuroimaging, www.fil.ion.ucl.ac.uk/spm) running under MATLAB 7.8.0 (MathWorks).…”
Section: Mrs Scanning Proceduresmentioning
confidence: 99%